Thermoelastic analysis of functionally graded carbon nanotube reinforced composite cylindrical panel embedded in piezoelectric sensor and actuator layers. (1st August 2016) - Alibeigloo, A.
Abstract: Based on theory of piezo-elasticity, bending behavior of functionally graded carbon nanotube reinforced composite (FG-CNTRC) cylindrical panel attached to thin piezoelectric layers subjected to thermal, mechanical loads and or electric field is investigated. It is assumed that thermo-elastic constants of the structure are independent of temperature gradient. In this paper, uniformly and various cases of functionally graded CNT distribution along the radial direction of host layer are considered. Governing differential equations are solved analytically by using the Fourier series expansion along axial and circumferential direction and state-space technique across the radial direction. Temperature, stress and displacement fields as well as induced electric voltage in sensor layer are obtained and used to study the thermo-piezoelastic behavior of hybrid FG-CNTRC cylindrical panel. Accuracy of present approach is validated by comparing the numerical results with the available reported results in literatures. Parametric studies are carried out to assess the effects of CNT volume fraction, case of CNT distribution along the radial direction, surface thermal/mechanical surface boundary conditions, applied voltage on the bending behavior of FG-CNTRC hybrid cylindrical panel.